From Artifact Decoding to Value Resonance: The Path of Cognitive Upgrading of Jiangnan Folk Crafts in Sino-foreign Humanities Exchange - Sun, Zhi-hao; Wang, Fucheng (Abdul Media Literasi, 2025)
As an essential cultural repository of Chinese civilization, the folk crafts of the Jiangnan region embody the collective memory and spiritual identity of vernacular society. Rooted in the theoretical framework of cultural communication and supported by five years of practical exploration, this study systematically investigates the functional pathways through which Jiangnan handicraft study programs facilitate Chinese and foreign humanistic exchanges. The research findings reveal several key insights: first, the intricate cultural symbol system embedded within Jiangnan folk crafts transcends linguistic barriers, enabling a deeper level of emotional resonance across different cultural contexts. Second, craft-based course design that fosters direct collaboration between Chinese and Western students significantly enhances the efficiency of cross-cultural cognitive processes, allowing for a more profound mutual understanding. Third, the study introduces and validates a structured three-phase model—skills transmission, narrative reconstruction, and creative symbiosis—which serves as an effective mechanism for transitioning cultural values from the realm of passive external observation to active intersubjective engagement. More specifically, this model facilitates the transformation of cultural perspectives from the gaze of the other into a dynamic inter-subjective dialogue, thereby fostering a more reciprocal and participatory form of cultural exchange. Through this framework, the study not only provides a theoretical paradigm with substantial academic depth but also offers practical guidance for the international dissemination of Jiangnan culture. By demonstrating how traditional folk crafts can serve as a conduit for intercultural communication and mutual understanding, this research contributes valuable insights into the broader discourse on global cultural sustainability, heritage preservation, and cross-cultural education.